2020
DOI: 10.3390/ijms21093264
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic Markers and Cytokines in OSA Patients

Abstract: The role of inflammation and dysfunction of the cholinergic system in obstructive sleep apnea (OSA) has not exhaustively clarified. Thus, in this study, we explore the non-neuronal cholinergic system and the balance of T helper (Th) 17- and T regulatory (Treg)-related cytokines in OSA patients. The study includes 33 subjects with obstructive sleep apnea and 10 healthy controls (HC). The expression levels of cholinergic system component, RAR-related orphan receptor (RORc), transcription factor forkhead box prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…However, no correlation was found between plasma choline levels and ESS scores. 43 Causes of the discrepancies in these studies remain unclear. Also, we cannot explain the association mechanism between lower plasma ACh levels and self-reported sleepiness.…”
Section: Discussionmentioning
confidence: 99%
“…However, no correlation was found between plasma choline levels and ESS scores. 43 Causes of the discrepancies in these studies remain unclear. Also, we cannot explain the association mechanism between lower plasma ACh levels and self-reported sleepiness.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, interest focus on exploring biomarkers has been increasing for decades. In recent years, additional research on cellular immune has reported that macrophage polarization towards M1 subsets ( Khalyfa, Kheirandish-Gozal & Gozal, 2018 ), increased ratio of NLR ( Rha et al., 2020 ), PLR ( Kıvanc et al., 2018 ), CD8+T/CD4+T ( Domagała-Kulawik et al., 2015 ), and Th17/Treg ( Reale et al., 2020 ), as well as DNA methylation of toll-like receptor 2/6 ( Huang et al., 2020 ) in OSA patients, suggesting possible reactions to new endogenous antigens. Given the vital role of T cells in adaptive immunity, the question arises as to why and how T cell immunity is impaired in OSA.…”
Section: Discussionmentioning
confidence: 99%
“…The possible mechanism includes changes in intrathoracic pressure, meaning that the increase in pleural negative pressure can lead to mechanical stretch of the aorta (54,55,(59)(60)(61), which further leads to the expansion of the aortic root, thoracic aorta and thoracic FL; patients with frequent intermittent hypoxia leading to oxidative stress and increases in sympathetic activity exhibit an increase in blood pressure due to the activation of the renin-angiotensin-aldosterone system (59,60,62). The state of chronic intermittent hypoxemia and the altered microenvironment in OSA patients, such as the increase in IL-6 levels and reduction in TGF-β levels, could damage the function of endothelial cells and promote a Th17/Treg imbalance, which leads to a reduction in the production of endotheliumdependent vasodilator substances and contributes to vascular dysfunction and stimulation of systemic inflammation (63)(64)(65)(66)(67).…”
Section: Discussionmentioning
confidence: 99%